### Nuprl Lemma : concat-lifting-2_wf

`∀[A,B,C:Type]. ∀[f:A ⟶ B ⟶ bag(C)].  (f@ ∈ bag(A) ⟶ bag(B) ⟶ bag(C))`

Proof

Definitions occuring in Statement :  concat-lifting-2: `f@` bag: `bag(T)` uall: `∀[x:A]. B[x]` member: `t ∈ T` function: `x:A ⟶ B[x]` universe: `Type`
Definitions unfolded in proof :  uall: `∀[x:A]. B[x]` member: `t ∈ T` concat-lifting-2: `f@`
Lemmas referenced :  concat-lifting2_wf bag_wf
Rules used in proof :  sqequalSubstitution sqequalTransitivity computationStep sqequalReflexivity isect_memberFormation introduction cut sqequalRule lambdaEquality lemma_by_obid sqequalHypSubstitution isectElimination thin hypothesisEquality hypothesis axiomEquality equalityTransitivity equalitySymmetry functionEquality isect_memberEquality because_Cache universeEquality

Latex:
\mforall{}[A,B,C:Type].  \mforall{}[f:A  {}\mrightarrow{}  B  {}\mrightarrow{}  bag(C)].    (f@  \mmember{}  bag(A)  {}\mrightarrow{}  bag(B)  {}\mrightarrow{}  bag(C))

Date html generated: 2016_05_15-PM-03_08_09
Last ObjectModification: 2015_12_27-AM-09_26_37

Theory : bags

Home Index